2021
DOI: 10.1002/2050-7038.13031
|View full text |Cite
|
Sign up to set email alerts
|

A reliable and efficient holomorphic approach to evaluate dynamic available transfer capability

Abstract: Summary In the present paper, the static approximate Newton‐Raphson‐Sidel (ANRS) and the developed down‐hill (DDH) algorithm methods were used. To take advantage of both methods, ANRS‐DDH and the revised holomorphic embedding load flow (RHELF) were combined. An approximation of the potential energy boundary surface (APEBS) was also employed in combination with determine transient stability and correct the previous methods. A combination of static method and transient stability led to a combined approach for dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…􏽥 Y − 1 is an N × N matrix implicitly indicating the bus 20) can be solved for 􏽥 V either iteratively or recursively. To solve the equation recursively, equations ( 16) and ( 20) are embedded with parameter, α as shown in (21) and (22). is embedding implies that α is a parameter for constant power injections.…”
Section: Proposed Implicit Z-bus Recursive Power Flow Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…􏽥 Y − 1 is an N × N matrix implicitly indicating the bus 20) can be solved for 􏽥 V either iteratively or recursively. To solve the equation recursively, equations ( 16) and ( 20) are embedded with parameter, α as shown in (21) and (22). is embedding implies that α is a parameter for constant power injections.…”
Section: Proposed Implicit Z-bus Recursive Power Flow Methodsmentioning
confidence: 99%
“…e authors in [19,20] showed the benefits from utilizing the HELM approach for three-phase unbalanced optimal power flow and for probabilistic power flow for small distribution test networks; however, the long time needed to solve the power flow equations impeded extending the application to larger distribution test networks. In [21,22], the authors notably used static approximate Newton-Raphson-Sidel (ANRS) and the developed down-hill (DDH) algorithm methods to derive a reliable and efficient holomorphic approach to evaluate dynamic available transfer capability and proposed distributed slack bus model formulation for the holomorphic embedding load flow method, respectively; however, Padé Approximation is still used.…”
Section: Introductionmentioning
confidence: 99%
“…X(k) (power series coefficient) is viewed as a transformation of x(t) at the k th order in differential transformation [27][28][29], as seen by (A6).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…The Holomorphic embedding load flow method (HELF) [28,29] is not needed to make any simplification assumptions for a non-iterative algorithm. HELF does not require any initial estimation and uses concepts within a complex analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation